2013
DOI: 10.1016/j.immuni.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The Interleukin-1 Family: Back to the Future

Abstract: Interleukin-1 (IL-1) is a central mediator of innate immunity and inflammation. The IL-1 family includes 7 ligands with agonist activity (IL-1α and β, IL-18, IL-33, IL-36α, β, γ), three receptor antagonists (IL-1Ra, IL-36Ra, IL-38) and an anti-inflammatory cytokine (IL-37). Members of the IL-1 Receptor (IL-1R) family include 6 receptor chains forming 4 signaling receptor complexes, two decoy receptors (IL-1R2, IL-18BP) and two negative regulators (TIR8 or SIGIRR, IL-1RAcPb). A tight regulation via receptor ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
1,524
1
46

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,654 publications
(1,598 citation statements)
references
References 149 publications
27
1,524
1
46
Order By: Relevance
“…and cytokines (IL-6, TNF-a, and TGF-b). 8 IL-1 stimulated thyroid cell proliferation and the in vitro production of IL-8. 9 In a study performed on 115 patients affected by a variety of thyroid conditions and 30 controls, IL-1b serum concentrations allowed discrimination between individuals with atrophic thyroiditis and those with PTC, which displayed the highest and the lowest values, respectively.…”
Section: Cytokinesmentioning
confidence: 91%
“…and cytokines (IL-6, TNF-a, and TGF-b). 8 IL-1 stimulated thyroid cell proliferation and the in vitro production of IL-8. 9 In a study performed on 115 patients affected by a variety of thyroid conditions and 30 controls, IL-1b serum concentrations allowed discrimination between individuals with atrophic thyroiditis and those with PTC, which displayed the highest and the lowest values, respectively.…”
Section: Cytokinesmentioning
confidence: 91%
“…The IL‐1 receptor antagonist (IL‐1 RA) is an endogenous inhibitor of IL‐1 that prevents the activation of the IL‐1 receptor by either IL‐1α or IL‐1β 21. IL‐1 RA is associated with a diverse range of diseases including CVD, type 2 diabetes, certain cancers and joint diseases such as arthritis 21, 22, 23, 24, 25. In a recent large‐scale Mendelian randomization study, it was found that genetically elevated levels of IL‐1 RA were causally associated with an increased risk of CHD and abdominal aortic aneurysm 26.…”
Section: Introductionmentioning
confidence: 99%
“…However, limited evidence shows the functions of SIGIRR in the liver. Previous tissue expression analyses showed that SIGIRR widely distributes in various tissues examined (2,50). However, the expression levels in tissues differ among various species.…”
Section: Discussionmentioning
confidence: 99%
“…Toll/IL-1R (TIR)8 or IL-1R8, is an important member of the TLR/IL-1R superfamily (1)(2)(3)(4). In contrast with other TIR family members, SIGIRR comprises a single extracellular Ig domain, a transmembrane region, and a conserved intracellular TIR domain with substitutions of the two amino acid sites (Ser 447 and Arg-Tyr 536 ) required for the signaling of IL-1RI, as well as a unique 95-aa-long cytoplasmic tail, which differentiates SIGIRR from other TIR-containing family members (4,5).…”
Section: S Ingle Ig Il-1r-related Molecule (Sigirr) Also Known Asmentioning
confidence: 99%